2022
DOI: 10.5897/ijeaps2021.0702
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of teachers motivation and professional development in public secondary schools in Kenya

Abstract: Teacher motivation is by and large the major determinant of students' success during the schooling process. This is primarily because a motivated teacher is likely to be more engaged and enthusiastic in the workplace. Kenya's education sector has in the recent past experienced industrial disharmony which has been occasioned by teachers' demand for higher remuneration. This demand, however, could be a pointer to the existence of other unmet needs among teachers in the country. This is what informed the study wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Advanced academic titles are typically associated with increased experience, knowledge, and skills in the educational field. Higher titles not only enhance teachers' income, but also their status and job satisfaction (Orina et al, 2022). Yu et al (2022) found that teachers with junior titles experienced lower job satisfaction and greater burnout than those with senior titles.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced academic titles are typically associated with increased experience, knowledge, and skills in the educational field. Higher titles not only enhance teachers' income, but also their status and job satisfaction (Orina et al, 2022). Yu et al (2022) found that teachers with junior titles experienced lower job satisfaction and greater burnout than those with senior titles.…”
Section: Discussionmentioning
confidence: 99%